The Rules of Human T Cell Fate in vivo - Costa del Amo, Pedro; Debebe, Bisrat; Razavi-Mohseni, Milad; Nakaoka, Shinji; Worth, Andrew; Wallace, Diana; Beverley, Peter; Macallan, Derek; Asquith, Becca (Frontiers in Immunology, 2020)
The processes governing lymphocyte fate (division, differentiation and death), are typically assumed to be independent of cell age. This assumption has been challenged by a series of elegant studies which clearly show that, for murine cells in vitro, lymphocyte fate is age-dependent and that younger cells (i.e. cells which have recently divided) are less likely to divide or die. Here we investigate whether the same rules determine human T cell fate in vivo. We combined data from in vivo stable isotope labelling in healthy humans with stochastic, agent-based mathematical modelling. We show firstly that the choice of model paradigm has a large impact on parameter estimates obtained using stable isotope labelling i.e. different models fitted to the same data can yield very different estimates of T cell lifespan. Secondly, we found no evidence in humans in vivo to support the model in which younger T cells are less likely to divide or die . This age-dependent model never provided the best description of isotope labelling; this was true for naïve and memory, CD4+ and CD8+ T cells. Furthermore, this age-dependent model also failed to predict an independent data set in which the link between division and death was explored using Annexin V and deuterated glucose. In contrast, the age-independent model provided the best description of both naïve and memory T cell dynamics and was also able to predict the independent dataset.